Can the Future-Like-Ours Argument Survive Ontological Scrutiny?. Issue 5 (16th October 2021) - Adams, Matthew; Rimell, Nicholas
Abstract: We argue that the future-like-ours argument against abortion rests on an important assumption. Namely, in the first trimester of an aborted pregnancy, there exists something that would have gone on to enjoy conscious mental states, had the abortion not occurred. To accommodate this assumption, we argue, a proponent of the future-like-ours argument must presuppose that there is ontic vagueness. We anticipate the objection that our argument achieves "too much" because it also applies mutatis mutandis to conscious humans. We respond by showing that an explanation can be given for why it is wrong to kill conscious humans that is independent of the underlying metaphysics. Our response brings into focus a reason why—at least in the context of an ethical argument like the future-like-ours argument—appeal to a highly controversial metaphysics is ad hoc. Such metaphysics is not necessary to explain the wrongness of killing conscious humans, only nonconscious fetuses.